Surface and Underground Water Level Monitoring Using Wireless Sensor Node with Energy Harvesting Support - Mihajlovic, Zivorad; Milosavljevic, Vladimir; Joza, Ana; Rajs, Vladimir; Damnjanovic, Mirjana; Zivanov, Milos (Elektronika ir Elektrotechnika, 2016)
In this paper development and testing of a wireless sensor node that is powered by solar energy harvesting is described. Implemented wireless sensor node is characterized by low cost and consumption, long mean time between maintenance, simplicity, flexibility, modularity and miniature design in applications for monitoring of environmental parameters. As a replacement for relatively expensive battery supply and in order to minimize maintenance costs, energy harvesting solution that uses a miniature solar panel and supercapacitor is tested. This node is used for measurements of water levels of surface and underground waters for application in agriculture. For this purpose the node is expanded with a capacitive sensor for measurement of water levels, which is particularly discussed in this paper as simple and innovative solution. DOI: http://dx.doi.org/10.5755/j01.eie.22.5.16346